Eles ousaram! Projeto História Nova do Brasil: as Reformas de Base começaram pela educação - Lima, Guilherme Pontieri de (Universidade Federal de São Carlos, 2017)
In the midst of the great effervescence of ideas, political manifestations, models and propositions of a nation in dispute, characteristic of the early 1960s, the Ministry of Education and Culture (MEC) supported a project to revise the teaching of History of Brazil. The project: the New History of Brazil, a set of monographs, carried out in a collaborative way between the Student Assistance Campaign (CASES), an organ linked to the MEC, and the Department of History of the Instituto Superior de Estudos Brasileiros (ISEB). as principal signatory Nelson Werneck Sodré. Such a revision of history teaching, launched in early 1964, was aborted months later by the dictatorship, which interrupted production, collected the work, persecuted the intellectuals associated with it, and labeled them generically as subversives. The possession of this material was attested to by subversion for the dictatorship. This present study seeks to analyze the project of the New History of Brazil in its relation with the so - called Brazilian reality. Capitalist development in Brazil did not present a single project of nation. It starts from the hypothesis that the New History of Brazil radicalized the national and anti-imperialist project and, extrapolating, the idea of the "basic reforms" in the educational field, was linked to the major project of the Brazilian revolution. Being propositive, the New History of Brazil extrapolated the field of education and teaching history, specifically, becoming more than an interrupted project, but a model to be fought.
They Dared! Project New History of Brazil: basic reforms started with education
Keywords: Ensino de História; História Nova do Brasil; História da Educação Brasileira; Reformas de base; Revolução brasileira; Brasil Pré-Golpe de 1964; Brasil República; Governo João Goulart; CASES; MEC; ISEB; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::HISTORIA DA EDUCACAO; CIENCIAS HUMANAS::HISTORIA::HISTORIA DO BRASIL::HISTORIA DO BRASIL REPUBLICA